Manifestasi Pemeliharaan Tuhan Dalam integritas Elia Pada panggilanya Analisis (1 Raja-raja 17: 1-6) - Ncihur Fronika Solin; Yersi Hotmauli Berutu (Jurnal Pendidikan Agama dan Teologi, 2024)
The reign of Ahab and his wife Jezebel was a time of spiritual crisis in Israel. Ahab did what was evil in God's eyes more than all those who preceded him (1Kgs. 16:30), he worshipped Baal and the gods that caused God's heartache and Elijah, the prophet sent by God in response to Ahab and Jezebel's deeds. Elijah opposed the worship of Baal. Elijah's integrity was seen in the great mission he carried out he followed what God commanded him but God's care for him did not escape God to provide what he needed and to do that God commanded him to bring food to Elijah in his hiding place. The research method used is the analysis of biblical texts, with a descriptive approach of analysis and literature review Descriptive analysis researchers use to describe God's providence to the prophet Elijah during the drought in Israel. Today, man as God's creation often doubts God's providence and is even able to do bad things before Him to fulfill his desires. Through Elijah it can be seen that if we believe and follow what he commands, God will take care of his created life and provide for his needs